‘AIClopedia’: How Does It Facilitate Gen-Z Students in Learning English? - Ni Luh Putu Ning Septyarini Putri Astawa; Putu Trisna Hady Permana (ELITE Association Indonesia, 2020)
Gen-Z has specific characteristics, one of the characteristics is being strongly connected to technology. It makes teachers nowadays should be able to facilitate them with technology-based learning media. One of the technologies that can be applied is Artificial Intelligence (AI). AI provides a self-directed learning activity where the students can learn by themselves using technology anywhere and anytime. This study aimed at developing a prototype design of AIClopedia (Artificial Intelligence Encyclopedia) by using the ADDIE method. AIClopedia is a learning media that can be used by the students in learning English which focuses on providing descriptive information of Indonesian endemic animals in two different languages (English and Bahasa Indonesia). The prototype has been judged by educational material and ICT media experts. The data of expert judgment rubrics showed that the prototype was categorized as excellent. It implied that the media can be used in facilitating Gen-Z students in Learning English.